Women’s empowerment in Tanzania Cashew Value Chain: Assessment of Opportunities and Constraints - Aku, Aika; Mather, David; Bryan, Elizabeth; Mpenda, Zena; Mpunde, Venance (International Food Policy Research Institute, 2023)
Cashew is one of the cash crops mostly grown by smallholder farmers in Tanzania. It provides a major source of rural employment and income. Women provide 90% of labor in small-scale cashew processing and largely sell to the domestic market. However, women face constraints in increasing the productivity and profitability of small processing operations. This study assesses the effectiveness of an intervention that provided equipment and training to women’s cashew processing groups (WCPGs) in the Mtwara and Lindi regions, implemented by the Small Industries Development Organization (SIDO). The study uses mixed methods including in-depth interviews with women processors and local experts, and a quantitative survey of the costs and benefits of small processing facilities. The study found that WCPGs using improved processing equipment achieved a 25% productivity gain, on average, compared with control group WCPGs. However, groups receiving the equipment still face some constraints, including accessing raw cashew. These constraints limit the extent to which efficiency and quality gains can be converted into higher income, and access to markets to sell processed cashew, forcing these WCPGs to rely on sales-agent intermediaries, reducing profits and increasing the risk of losses. The effectiveness of the SIDO intervention was further limited by lack of cohesion of some groups. The results suggest that such interventions need to take a more holistic approach, recognizing the multiple challenges women face in agri-food systems. In addition to processing equipment, the SIDO intervention should target experienced, well-functioning processing groups; provide training on group management; facilitate market access and contract enforcement.